2005
DOI: 10.1111/j.1462-5822.2005.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

The InhA1 metalloprotease allows spores of the B. cereus group to escape macrophages

Abstract: SummaryBacteria of the Bacillus cereus group are resistant to the immune systems of various hosts and establish potent infections, implying that bacteria circumvent the bactericidal activity of host phagocytic cells. We investigated the fate of Bacillus spores after their internalization by macrophages. We found that these spores survive and escape from macrophages, and that the bacterial metalloprotease InhA1, the major component of the exosporium, is essential for efficient spore release from macrophages. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 33 publications
2
90
0
1
Order By: Relevance
“…We have previously shown that spores of the ⌬inhA1 mutant were retained inside macrophages, whereas spores of the wildtype B. thuringiensis strain 407 were capable of escaping from the cells (50). However, spores of the 407 ⌬inhA2 and 407 ⌬inhA3 mutants are still capable of escaping from macrophages (data not shown), implying that only InhA1 is involved in this process.…”
Section: Vol 192 2010mentioning
confidence: 71%
See 2 more Smart Citations
“…We have previously shown that spores of the ⌬inhA1 mutant were retained inside macrophages, whereas spores of the wildtype B. thuringiensis strain 407 were capable of escaping from the cells (50). However, spores of the 407 ⌬inhA2 and 407 ⌬inhA3 mutants are still capable of escaping from macrophages (data not shown), implying that only InhA1 is involved in this process.…”
Section: Vol 192 2010mentioning
confidence: 71%
“…Spore release infection experiments and cytotoxicity assays on J774 murine macrophage-like cells were performed as previously described (49,50 Infection by injection into the hemolymph of Galleria mellonella or Bombyx mori larvae was performed as described previously (17,52). For groups of 15 last-instar larvae, the base of the last proleg was injected with a 10-l suspension containing 7.5 ϫ 10 3 vegetative bacteria or spores for G. mellonella, or 50 vegetative bacteria for B. mori.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the spores are known as the dormant form of bacteria, many spore-associated enzyme activities have been identified, especially those of Bacillus species, where proteases are crucial for spore germination (Hilbert & Piggot, 2004). In addition, some sporeassociated proteases contribute to the virulence of bacteria (Ramarao & Lereclus, 2005). With regard to Thermoactinomyces species, esterase activity has been detected in the spores of Thermoactinomyces vulgaris by using fluorogenic substrates (Gazenko et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Dozens of proteins, including a putative NH, were identified from the exosporia of B. cereus and B. anthracis spores (Redmond et al, 2004;Steichen et al, 2003;Todd et al, 2003). Although the role of some proteins has been studied, most functions remain to be elucidated (Boydston et al, 2006;Ramarao & Lereclus, 2005;Steichen et al, 2005;Yan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%